Model-Model Komunikasi Dakwah (Studi Terhadap Dakwah di Kota Padang) - Irta Sulastri (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Da'wah is not only a religious activity mosque or place of worship, preaching today comes and touches the various facets of life and are found in a variety of events. The development is characterized by the propaganda of the vast territory into and media used, and uses an approach that leads to the audience or mad'unya criteria. This study aims to gain propaganda communication models used preachers, using qualitative. Propaganda communication model applied preacher in preaching consists of dialogue models, models monologue, narrative models, models and models muhasabah demonstration or pilot. The model used preachers nothing is single, but is a combination of models suitable communications are considered suitable to the situation of pilgrims.